Peningkatan Kualitas Produksi Gula Aren dengan Modernisasi Peralatan Bagi Petani di Kasepuhan Sinar Resmi, Cisolok, Sukabumi - Didik Sugiyanto; Erwin, Erwin; Aisa Aulia; Sulandari, Uci; Ngesti Rahaju, Sri Mumpuni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Indonesia possesses rich biodiversity with the potential to serve as a source of economic growth, one example being the sugar palm plant (Arenga pinnata) found in Kasepuhan Sinar Resmi, Sukabumi Regency. This community service activity aims to address challenges in the traditional palm sugar processing methods, which are time- and energy-consuming, as well as in marketing management, which remains underdeveloped. The activities were carried out through several stages: preparation, implementation, evaluation, and monitoring. During the implementation stage, modernized equipment for palm sugar processing was developed to simplify and improve the traditional methods. In addition, training in information technology-based marketing management was provided. As a result of the activity, farmers experienced improved skills and convenience in processing palm sugar using modern tools such as a palm sap mixer and a palm sugar sieving machine. The processed products became cleaner, and the processing time was reduced from 5 hours to 3–4 hours, thereby accelerating production and improving output quality. Furthermore, there was a significant increase in farmers' knowledge of digital marketing strategies.